The impact of control on national-scale livestock disease outbreaks in the United States - Smith, Samuel M., author; Webb, Colleen T., advisor; Beck-Johnson, Lindsay M., committee member; Keller, Kayleigh, committee member (Colorado State University. Libraries, 2023)
Outbreaks of livestock diseases, like foot-and-mouth disease (FMD) and bovine tuberculosis (bTB), pose a significant economic threat to the United States livestock industry. Significant interest then lies in developing strategies to mitigate the impact of an outbreak should they occur. This thesis explores the effect of control interventions on outbreaks of FMD and bTB in the U.S. In chapter one, I weigh trade-offs associated with delaying the implementation of control on the economic impact of controlling an FMD outbreak in the U.S. This study aimed to understand whether control policies that adopt a conservative initial approach, but may be updated as an outbreak progresses, can reduce socioeconomic harm while achieving desired outbreak outcomes. I find that delaying the implementation of all available control interventions early on in an outbreak does not reduce the cost of small outbreaks and exacerbates the largest outbreaks, suggesting that the potential benefits of this type of adaptive response may be out weighted by the risk of allowing a large outbreak to become worse. Next, I investigate how the culling of infected cattle premises, diagnostic testing, and traceback investigations impact the size of bTB outbreaks. Results from this study show improvements to traceback investigations result in the largest decreases in bTB outbreak size, which suggests that improving the identification of premises via traceback investigations is more important than increasing antemortem diagnostic sensitivity. Although this thesis focuses on the control of livestock disease, we can abstract several broader principles that contribute to ecology and epidemiology's understanding of disease dynamics. Both chapters demonstrate the importance of a population's underlying demography to determining an outbreak's overall trajectory as well as minimizing the time until detection of an infection and the time until control is implemented.
Keywords: emergency disease management; livestock epidemiology; trace investigations; foot and mouth disease; bovine tuberculosis; state-dependent control